The optimization of Al Maidah catering home business through financial records and marketing management - Syah Amelia Manggala Putri (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
Yogyakarta is known as a city center of education, cultural center as well as a tourist destination by both domestic and international tourists. This condition really supports the development of a home-based culinary business, especially catering. Al Maidah Catering is a home-based business managed by the millennial generation with good and stable development. The problems faced in the development of Al Maidah Catering home business are the absence of recording financial statements and the absence of an effective and efficient marketing strategy implementation. The absence of recording financial reports and marketing management cause the performance of Al Maidah Catreing's home business being less optimal. The purpose of this service is to provide solutions to these problems by conducting training and assistance in recording financial reports as well as marketing management training and assistance. The result of this training is that partners have been able to record simple financial reports and apply marketing management which has a positive effect on increasing sales, by carrying out online marketing strategies for Al Maidah Catering's home business through IG Ads which are proven to be effective and efficient